PEMBERIAN LIMBAH CAIR BIOGAS SEBAGAI PUPUK ORGANIK PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Lamro Tua Siregar; Wardati '; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to know the dosage of the best bioslurry as organic fertilizer to support the growth of oil palm in main nursery. This research is conducted by using Complete Random Design (CDR) consist of 6 treatments and each treatment was repeated 4 times then obtained 24 experimental units, each experimental unit consist of 2 plants. The treatments are; LB0 : without bioslurry treatment, LB1 : 50 ml bioslurry/plant, LB2 : 100 ml bioslurry/plant, LB3 : 150 ml bioslurry/plant, LB4 : 200 ml bioslurry/plant, LB5 : 250 ml bioslurry/plant.The result of this research shows that the aplication of giving bioslurry has a real effect to increase the number of leaves and dry weight, and not effect et the height parameter of the oil palm, hump diameter, root volume, and root crown ratio. Aplication of 200 ml bioslurry dosage give the best result on oil palm growth in main nursery. Keywords: oil palm, bioslurry, dosage.